The Students’ Learning Style Used In Learning English at MAN Morowali - Ingriyani Yohana Rawung (Sintuwu Maroso Journal of English Teaching, 2020)
This research aims to describe learning style of the students in learning English at MAN Morowali. Design of this research is qualitative research. The instruments of this research are questionnaire and documentation. Data are gained by the result of questionnaire and documentation. The result of this research obtains that the learning style of Eleven grade students in learning English At MAN Morowali are classified into major, minor, negligible learning style preferences. The major learning style are visual, auditory, kinesthetic, tactile, group and individual. On the other hand sometime minor learning style are visual, group and individual